The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/aps.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting effects of isobavachin on neurogenesis of mouse embryonic stem cells were associated with protein prenylation

Abstract: Aim: Some small molecules can induce mouse embryonic stem (ES) cells to differentiate into neuronal cells. Here, we explored the effect of isobavachin (IBA), a compound with a prenyl group at position 8 of ring A, on promoting neuronal differentiation and the potential role of its protein prenylation. Methods: The hanging drop method was employed for embryonic body (EB) formation to mimic embryo development in vivo. The EBs were treated with IBA at a final concentration of 10 -7 mol/L from EB stage (d 4) to d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It has been shown that flavonoids are key compounds for the development of a new generation of therapeutic agents that are clinically effective in treating neurodegenerative diseases [ 34 ]. Our previous work found that ICT [ 22 ] and IBA [ 23 ] had significant neurogenesis-inducing activities. Based on the core molecular scaffolds, a synthetic flavonoid library was designed and synthesized, with 2”, 3”-unsaturated alkyl groups at C-8 position as well as hydroxy or methoxy groups at different positions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that flavonoids are key compounds for the development of a new generation of therapeutic agents that are clinically effective in treating neurodegenerative diseases [ 34 ]. Our previous work found that ICT [ 22 ] and IBA [ 23 ] had significant neurogenesis-inducing activities. Based on the core molecular scaffolds, a synthetic flavonoid library was designed and synthesized, with 2”, 3”-unsaturated alkyl groups at C-8 position as well as hydroxy or methoxy groups at different positions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such molecules will likely provide new insights into mitochondrial metabolism in neuronal differentiation of ES cells, and may ultimately contribute to effective medicine for tissue repair and regeneration [ 21 ]. Our previous work showed that some natural flavonoid compounds, icaritin (ICT) [ 22 ] and isobavachin (IBA) [ 23 ] had significant neurogenesis-inducing activities. In the present study, we used a newly-screened flavonoid compound 4a as a probe of underlying biology, and aimed to elucidate PPARs expressions and several elements of cellular energy metabolism in neuronal differentiation of mouse ES cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cleavage of Retro Diels Alder (RDA) is its main characteristic fragmentation of aglycones. [7,8] The 1,3 A+ ion at m/z 149.025 was identified as the diagnostic ion ( Figure S1A). According to the absence or presence of m/z 149.025, we could characterize the oxidation position of isobavachin.…”
Section: Identification Of Isobavachin-related Metabolites In Micementioning
confidence: 99%
“…Icariin bMSCs Enhanced differentiation → osteoblasts, associated with increased TGFβ1 and BMP2 [12] mESCs Enhanced differentiation → cardiomyocytes; ROS, p38signalling was involved [30,31] Desmethylicaritin mESCs Enhanced differentiation → cardiomyocytes [30] Baicalin bMSCs Enhanced differentiation → neurons [17] ucMSCs Enhanced differentiation → neurons [22] NSCs Enhanced differentiation → neurons [26] Salvianolic acid B bMSCs Enhanced differentiation → cardiomyocytes [20] mESCs Enhanced differentiation → cardiomyocytes when combined with vitamin C [34] Rg1 bMSCs Enhanced differentiation → cardiomyocytes when in synergy with 5-azacytidine [21] Isobavachin mESCs Enhanced differentiation → neurons or astrocytes, increased ERK, decreased p38, JNK were involved [32] Isopsoralen bMSCs Proliferation ↓, enhanced differentiation → osteoblasts [13] Osthole bMSCs Proliferation ↓, enhanced differentiation → osteoblasts [14] Astragaloside bMSCs Proliferation ↑, stem cell factor was increased [16] Ligustrazine bMSCs Enhanced differentiation → neurons [18] Geniposide NSCs Enhanced differentiation → neurons [26] Salidroside bMSCs Enhanced differentiation → neurons [19] NSCs Enhanced differentiation → neurons [24] Naringin bMSCs Enhanced differentiation → osteoblasts; MAPK signaling was involved [15] Ginkgolide B mESCs Increased apoptosis, increased JNK activation, ROS formation was involved [33] Antler polypeptides NSCs Enhanced differentiation → neurons [25] Notes: mESC: mouse embryonic stem cells; bMSCs: bone mesenchymal stem cells; NSCs: neural stem cells; ucMSCs: umbilical cord blood mesenchymal stem cells; TGF: transformation growth factor; BMP: bone morphogenetic protein; ROS: reactive oxygen species; PI3K: phosphoinositide 3-kinase; Akt: also known as protein kinase B; ERK: extracellular signaling-regulated kinase; JNK: c-Jun N-terminal kinase; MAPK: mitogen-activated protein kinase our understanding of the role of stem cells in the pathogenesis of abnormal emotions, development, stressors, behaviors, and aging. Neurogenesis in adult male Sprague Dawley rats has been extensively analyzed in the forebrain and hippocampal formation, and different stress paradigms (emotional, systemic, psychological, or physical) have been reported to decrease progenitor cell proliferation and the production of immature neurons in the hippocampal dentate gyrus in many mammalian species.…”
Section: Compound Type Of Stem Cells Main Outcome and Mechanisms Refementioning
confidence: 99%
“…initiated the ICA-inducible differentiation cascade, including activation of the p38 mitogenactivated protein kinase (MAPK) pathway (30,31). Isobavachin, a major component of Malaytea Scurfpea, was shown to induce differentiation of mouse ESCs into neurons and astrocytes under different conditions that involved decreased phosphorylation of p38 and JNK and increased ERK phosphorylation (32). Ginkgolide B, a chemical component extracted from Ginkgo Biloba leaves, was reported to induce mouse ESC apoptosis via ROS generation, c-Jun N-terminal kinase (JNK) activation, loss of mitochondrial membrane potential (MMP), and caspase-3 activation (33).…”
mentioning
confidence: 99%